Evaluation of Dinacharya in the Context of Netra - Shivani kapurkar; Ch. Ramadevi (International Journal of Ayurveda and Pharma Research, 2023)
“Sarvaendriynam Nayanam Pradhanam” Chakshurindriya (eye) has been given utmost importance among all the sense organs i.e., nose, ear, eyes, tongue, skin by all the Acharyas. So, it must be protected wisely. Many eye disorders, including refractive errors, dry eye, computer vision syndrome, age-related macular degeneration, cataract, hypertensive retinopathy, diabetic retinopathy, and glaucoma, have been linked to the changing lifestyle of the modern era. This is especially with regard to the busy modern lifestyle and prolonged use of digital screens in our daily lives, from smartphone’s to computers. The daily routine for eye care as explained in Dincharya (daily regimen), involves a combination of preventive measures, therapeutic practices and lifestyle adjustments. These practices aim to balance the Doshas (internal energies) Vata, Pitta, Kapha associated with eye health. Ayurveda aims at prevention and cure of diseases and explains in detail the Rutucharya, Dinacharya, Sadvritta. In, eye care the Dincharya (daily regimen) includes Anjana (collyrium), Abhyanga (massage), Nasya (nasal instillation of drugs), Snana (bathing), Netraprakshalana (eye wash), Padabhyanga (foot massage), Padaprakshalana (cleaning of foot), and Padatra Dharana (use of footwear), Chhatra dharana, Netra Vyayama (eye exercise). Due to hazardous lifestyle, many people are not taking proper care of own self’s in the right way. Here, this review article explores the application of Dinacharya (daily regimen) principles specifically tailored for eye care, emphasizing a holistic approach to maintain ocular health.